Expression of Chemokine Genes in Murine Macrophages Infected with Orientia tsutsugamushi - Cho, Nam-Hyuk (American Society for Microbiology, 2000)
Scrub typhus, caused by Orientia tsutsugamushi infection, is characterized by local as well as systemic inflammatory manifestations. Inflammation is initiated by O. tsutsugamushi-infected macrophages and endothelial cells in the dermis. We investigated the regulation of chemokine induction in macrophage cell line J774A.1 in response to O. tsutsugamushi infection. The mRNAs for macrophage inflammatory proteins 1α/β (MIP-1α/β), MIP-2, and macrophage chemoattractant protein 1 were induced within 30 min, and their levels showed a transitory peak for 3 to 12 h. However, the lymphotactin, eotaxin, gamma interferon-inducible protein 10, and T-cell activation gene 3 mRNAs were not detected by RNase protection assays. Heat-killed O. tsutsugamushi induced a similar extent of chemokine responses. Induction of the chemokine genes was not blocked by the eukaryotic protein synthesis inhibitor cycloheximide, suggesting that de novo synthesis of host cell protein is not required for these transcriptional responses. The induction of chemokine mRNAs by O. tsutsugamushi was blocked by the inhibitors of NF-κB activation. Furthermore, O. tsutsugamushi induced the nuclear translocation and activation of NF-κB. These results demonstrate that heat-stable molecules of O. tsutsugamushi induce a subset of chemokine genes and that induction involves activation of the transcription factor NF-κB.